Implementation and Obstacles to Student Character Education at SMAN 1 Anjir Muara - Nor Aniah; Ersis Warmansyah Abbas; Mutiani Mutiani; Raihanah Sari; Jumriani Jumriani (The Innovation of Social Studies Journal, 2024)
The character can be formed through education, one of the institutions that can carry out character education is the school. One of the means for building student character in schools is through the learning process, school culture, and extracurricular activities. This study aims to describe the implementation of character education for students at SMAN 1 Anjir Muara and find out the obstacles at SMAN 1 Anjir Muara in implementing character education for students. The approach used in this study uses a qualitative descriptive approach. The observation, interview, and documentation techniques were used to collect data obtained from informants or institutions related to this research. To analyze the data in this study used data reduction techniques, data display, and verification.The results of this study state that character education at SMAN 1 Anjir Muara is implemented through integration into learning activities including developing character values in learning tools such as lesson plans; school culture is classified into three types of activities, namely routine, spontaneous, and exemplary activities; and extracurricular activities such as scouting, osis, and PMR. In addition, there are obstacles in the implementation of character education for students at SMAN 1 Anjir Muara, who come from the family environment and technological advances that are not in line with the education implemented in the school environment.